Development of the on-demand fuel injection system for a light truck using the hydrogen enriched compressed natural gas (HCNG) fuel - Watechagit, Sarawoot; Panduang, Ruangdet; Prommakorn, Natthaporn; Siriput, Peeraya; Achawangkul, Yaowateera; Chullabodhi, Bunyongvut (Engineering and Applied Science Research, 2014)
The use of hydrogen as a fuel by mixing with a commercial fuel has recently been investigated continuously in order to solve the energy crisis and global warming. This article presents the results of the design and experimentation for the use of the hydrogen enriched compressed natural gas or HCNG as a fuel. The prototype vehicle a light truck equipped with a 1809 cc. gasoline engine. The proposed system is a mixing system where the compressed natural gas and the hydrogen are stored on-board and controlled separately. They are mixed as they are injected into the intake manifold right before the intake-port (Port Injection). The hydrogen supply system used in this investigation is adopted from the common system used for compressed natural gas system. The mixing ratio (%H in the total volume of HCNG) ranges from 5% to 20% by volume. The performance testing is done through the Chassis Dynamometer. The results show that the power and the torque of the engine drops when using either CNG or HCNG as compared to the gasoline fuel. However, when compared to the case when using the CNG, the 10% addition of hydrogen can increase the performance by 1%. The performance, on the other hands, is reduced for other amount of hydrogen additions.